Character Preferences in Competitive Games: A study among League of Legends players - Laato, Samuli; Karaosmanoglu, Sukran; Hamari, Juho; Brunnhofer, Marlies; Kordyaka, Bastian (United States, 2025)
Various multiplayer online games, such as League of Legends, offer players a selection of characters from which they can choose one to play with. In the case of League of Legends, these characters (called champions) differ in terms of game mechanics, appearance, and lore. Understanding the reasons behind players' champion preferences can help designers create more engaging playable characters. Therefore, in this study, we investigated qualitatively how League of Legends players (N=34) justify their champion preferences. Our findings revealed mechanics and gameplay as the most dominant given reasons in almost all contexts for both positive and negative preferences. Champion aesthetics and lore were mentioned in connection to individual champions, but also in relation to the overall representativeness of the game's champion pool. We found evidence that the in-game player cultures were shaping particularly which champions players disliked. Interestingly, female participants rarely mentioned gender as an important characteristic when justifying their champion preferences, but were overwhelmingly choosing female champions as their favorites. These findings warrant further study into, for example, the apparent asymmetry in how players of different genders develop and form their character preferences.
Proceedings of the 58th Hawaii International Conference on System Sciences